The Role of Financial Administration Staff In Managing Petty Cash In The General Engineering Division of PT PAL Indonesia - Yasah, Aulya Difta; Nugroho, Rusdi Hidayat (Business and Investment Review, 2024)
Financial administration staff play an important role in ensuring the smooth functioning of the company's operations, especially in petty cash management. In the General Engineering Division of PT PAL Indonesia, petty cash management is one of the crucial elements to support daily operational needs. Therefore, highly competent financial administration staff are required to handle these tasks properly. This study aims to analyze the role of financial administration staff in managing petty cash at the General Engineering Division of PT PAL Indonesia which focuses on the tasks and obstacles faced. The method used in this research is a qualitative approach, with data collection techniques in the form of interviews and direct observation to financial administration staff. The results showed that financial administration staff have an important role in managing petty cash, which consists of six stages of tasks, from the establishment to reporting the use of petty cash funds. In addition, this study also identified several obstacles faced in petty cash management. From this study, it can be concluded that the role of financial administration staff is very significant in maintaining the efficiency and effectiveness of petty cash management, which directly supports the overall performance of the General Engineering Division of PT PAL Indonesia.